Thermodynamic and kinetic stability of intermolecular triple helices containing different proportions of C+*GC and T*AT triplets. - James, P; Brown, T; Fox, K (2003)
We have used oligonucleotides containing appropriately placed fluorophores and quenchers to measure the stability of 15mer intermolecular triplexes with third strands consisting of repeats of TTT, TTC, TCC and TCTC. In the presence of 200 mM sodium (pH 5.0) triplexes that contain only T.AT triplets are unstable and melt below 30 degrees C. In contrast, triplets with repeats of TTC, TCC and CTCT melt at 67, 72 and 76 degrees C, respectively. The most stable complex is generated by the sequence containing alternating C+*GC and T*AT triplets. All four triplexes are stabilised by increasing the ionic strength or by the addition of magnesium, although triplexes with a higher proportion of C+*GC triplets are much less sensitive to changes in the ionic conditions. The enthalpies of formation of these triplexes were estimated by examining the concentration dependence of the melting profiles and show that, in the presence of 200 mM sodium at pH 5.0, each C+*GC triplet contributes about 30 kJ x mol(-1), while each T*AT contributes only 11 kJ x mol(-1). Kinetic experiments with these oligonucleotides show that in 200 mM sodium (pH 5.0) repeats of TCC and TTC have half-lives of approximately 20 min, while the triplex with alternating C+*GC and T.AT triplets has a half-life of approximately 3 days. In contrast, the dissociation kinetics of the triplex containing only T*AT are too fast to measure.